The Sandwich Generation and Cryptocurrencies: Trust, Product Knowledge and Reference Group as Triggers of Investment Intention - Ignatius Hari Santoso; Widhian Hardiyanti; Mulyo Budi Setiawan (UNIVED Press, 2024)
The rise and evolution of Cryptocurrency has been continuous since the launch of Bitcoin in 2009. However, Cryptocurrency as an investment instrument has not been able to attract the attention of young people. Moreover, the legal basis of trading involving Cryptocurrencies still has the potential to change, thus there could be concerns over the legality of Crypto assets as an investment medium. This research seeks to prove the effectiveness of several predictors such as trust, product knowledge and reference groups in shaping the intention to invest in Cryptocurrency. The result is that among the 3 constructs used in the measurement, only the Product Knowledge construct has a significant impact on the formation of intention to invest in Cryptocurrency